Non-vitamin K oral anticoagulants associated bleeding and its antidotes - Steiner, Thorsten; Köhrmann, Martin; Schellinger, Peter D.; Tsivgoulis, Georgios (Journal of stroke, 2018)
Oral anticoagulant-associated intracerebral hemorrhage (OAC-ICH) accounts for nearly 20% of all ICH. The number of patients with an indication for oral anticoagulant therapy (OAT) increases with increasing age. OAT became less complicate with the introduction of non-vitamin K oral anticoagulants (NOAC) OAT because of easier handling, favorable risk-benefit profile, reduced rates of ICH compared to vitamin K antagonists and no need for routine coagulation testing. Consequently, despite a better safety profile of NOAC the number of patients with OAC-ICH will increase. The mortality and complication rates of OAC-ICH are high and therefore they are the most feared complication of OAT. Immediate normalization of coagulation is the main goal and therefore knowledge of pharmacodynamics and coagulation status is essential. Laboratory measurements of anticoagulant activity in NOAC patients is challenging as specific tests are not widely available. More accessible tests such as the prothrombin time and activated partial thromboplastin time have important limitations. In dabigatran-associated ICH 5 g Idarucizumab should be administered. In rivaroxaban and apixaban-associated ICHs administration of andexanet alpha should be considered. Prothrombin complex concentrate may be considered if andexanet alpha is not available or in case of an ICH associated with edoxaban.
Gesehen am 14.04.2020